A 90-Day Oral Toxicological Evaluation of the Methylurate Purine Alkaloid Theacrine - Amy Clewell; Gábor Hirka; Róbert Glávits; Philip A. Palmer; John R. Endres; Timothy S. Murbach; Tennille Marx; Ilona Pasics Szakonyiné (Journal of Toxicology)
A 90-day repeated-dose oral toxicological evaluation was conducted according to GLP and OECD guidelines on the methylurate purine alkaloid theacrine, which is found naturally in certain plants. Four groups of Hsd.Brl.Han Wistar rats (ten/sex/group) were administered theacrine by gavage doses of 0 (vehicle only), 180, 300, and 375 mg/kg bw/day. Two females and one male in the 300 and 375 mg/kg bw/day groups, respectively, died during the study. Histological examination revealed centrilobular hepatocellular necrosis as the probable cause of death. In 375 mg/kg bw/day males, slight reductions in body weight development, food consumption, and feed efficiency, decreased weight of the testes and epididymides and decreased intensity of spermatogenesis in the testes, lack or decreased amount of mature spermatozoa in the epididymides, and decreased amount of prostatic secretions were detected at the end of the three months. At 300 mg/kg bw/day, slight decreases in the weights of the testes and epididymides, along with decreased intensity of spermatogenesis in the testes, and lack or decreased amount of mature spermatozoa in the epididymides were detected in male animals. The NOAEL was considered to be 180 mg/kg bw/day, as at this dose there were no toxicologically relevant treatment-related findings in male or female animals.